Assessing infant feeding attitudes of women during pregnancy - Simin Dragana; Vidaković Snežana; Šćepović Miljana (Association of Nurses Technicians and Midwives, 2018)
Introduction: Breast milk is the optimal source of nourishment for babies up until the age of 6 months. Promotion of breastfeeding reflects public health policies, however an insufficient number of expectant mothers are aware of official the recommendations and the significance of breastfeeding. Socio-demographic characteristics of expectant mothers such as age, education and income, can modify attitudes towards breastfeeding. Positive attitudes of expectant mothers towards starting and continuing to breastfeed are an important component of proper child growth and development. Goal: The main goal of this study was to assess the knowledge and attitudes of expectant mothers about breastfeeding, and establishing if there is a difference in attitudes of expectant mothers in relation to their socio-demographic characteristics. Material and methods: Research was conducted as a cross section study by conducting a survey of 107 expectant mothers that have attended the School for expectant mothers at the community health centre in Novi Sad. The survey consisted of socio-demographic questions and the Iowa Infant Feeding Attitude Scale, IFFAS. Data processing included methods of descriptive and inferential statistics. Program pack SPSS (version 21) was used. Values of p<0,05 were considered statistically significant. Results: More than two thirds of expectant mothers had a neutral position towards breastfeeding. Socio-demographic characteristics of expectant mothers do not influence the knowledge and attitudes towards breastfeeding and the application of artificial baby milk in nourishment of children. Conclusion: Knowing the attitudes that expectant mothers have of starting to and continuing to breastfeed is essential for the development activities and methods of adequate informing about breastfeeding. Results received indicate to the necessity of education through which future mothers and other family members would be acquainted with information that would positively impact their attitudes towards breastfeeding.